A novel cogging torque measurement method for multi slot/pole permanent magnet motor - Wanwan Zhu; Yukai Yang; Hongzhou Song; Yinan Liu; Zaiping Zheng; Yiguang Chen (IET Electric Power Applications, 2023)
Abstract The adverse effect on speed ripple and vibration makes it necessary to evaluate the cogging torque. Due to the tolerance of stator and rotor stacks as well as nonuniform magnetization of permanent magnet, the amplitude of cogging torque is unequal in different rotor position. As a result, the verification of theoretical analysis becomes difficult. Therefore, the cogging torque average is used to weigh it. In view of the large least common multiple of multi slot/pole Permanent magnet motor, which means, there are multiple cogging torque cycles per rotor revolution, a cogging torque measurement method is proposed. Through simple devices such as arm, weight, digital gauge, resolver, and so on, the amplitude and period of cogging torque can be accurately measured without site restrictions. The correctness of the method is verified by simulation and experiment, and that can be used as a supplement to cogging torque evaluation for multi slot/pole PMM.